How does it feel to travel through a tunnel? - Ditte Bendix Lanng (Ambiances)
This paper opens a pathway for a constructive vision of atmospheric qualities of transit space design. It focuses on an ordinary tunnel for pedestrians and cyclists in a suburban district of Aalborg, Denmark. By way of functionalist design and traffic segregation the tunnel facilitates the passage of daily life journeys. Through unpacking concrete mobile situations that occur on a journey home from school and through speculative architectural explorations into a possible re-design of the tunnel, an underused potential is identified for transit space to be a sensorial and social public space. One way of approaching this potential, it is argued, is to work with transit spaces as atmospheric spaces of wayfaring, drawing to the forefront of design considerations the affective engagement between travellers and the material environment. Inherent in this proposition is a critique of the assumptions that daily life travelling can be reduced to a desensitized and passive transport practice and that transit spaces are placeless.